The Implication of Communication Framework towards The Selayah Keringkam as a Form of Communication - Qistina Donna Lee, Abdullah; Norsyahbany, Mansor (Human Resource Management Academic Research Society, 2021)
The role of communication in embroidery has increased through the diversity of cultural or heritage. Motif in textile possess an important communicative role as an extension of spoken and written language. This research focuses on motif of Selayah Keringkam embroidery as a content to be delivered through communication channels, 4C’s Effective Communication that consists of Comprehension, Connection, Credibility and Contagiousness. Mix methods have been using in this study by distributing 50 set of questionnaires and in-depth interview session with related authorities. Conceptual framework in this study aims to position Selayah Keringkam embroidery among tourist to raise awareness of this cultural product.